Tuberculous Spondylitis (Revista de Medicina Clinica, 2023)
Clinical snapshot on Tuberculous Spondylitis presented in volume 7 number 1 of 2023 of the Journal of Clinical Medicine
Keywords: Tuberculous spondylitis; Infection